First Principle Study on AlN Nano Wire - Tuoc, Vu Ngoc; Minh, Nguyen Viet (Communications in Physics, 2012)
We present a first-principle study on the atomic and electronic structure of AlN Nanowire and examine the dependence of surface stress on nanowire lateral size and shape. The hexagonal wire size ranging as 10-16-22Å\ and triangular wire ranging from 10-13-16-20Å. We investigate the unsaturated dangling bond state in the region of bandgap with varying the wires diameter. We also calculated the surface formation energy and find that it decreases with increasing the wire diameter and a greater stability (lower surface formation energy) comes with hexagonal wires. We also study the dependence of theoretical prediction on various density functional theory (DFT) treatment using Dmol3 local orbital density functional method with an effective core potential.